Impacto laboral de Wal-Mart en la productividad laboral. Un análisis por municipio en México; Labor impact of Wal-Mart on labor productivity: an analysis by municipality in Mexico - Vićtor Manuel Castillo Giroń; Manuel Machuca Martińez; Suhey Ayala Ramirez (Small Business International Review (SBIR), 2019)
Si bien antes de los an\~os 1990 ya habiá participacioń de grandes empresas minoristas en Mex́ico, la llegada de empresas transnacionales, como Wal-Mart, generoúna reconfiguracioń en la distribucioń de alimentos y, con ello, una expectativa del impacto directo sobre algunas variables del sector. Nuestro objetivo es determinar si la presencia de Wal-Mart implica una mayor productividad por trabajador. Para ello se construyoún modelo de probabilidad logiśtica ordinal cuyos resultados a nivel municipal muestran una relacioń positiva y estadiśticamente significativa, es decir, la probabilidad de encontrar un mayor nivel de productividad aumenta con una mayor presencia de dicha empresa. – – Although before the 1990s there was already participation of large retail companies in Mexico, the arrival of transnational companies, such as Wal-Mart, generated a reconfiguration in food distribution and, with this, an expectation of the direct impact on some sector variables. Our objective is to establish if Wal-Marts presence involves a higher productivity per worker. To achieve this goal, an ordinal logistic probability model was constructed and its results at municipal level show a positive and statistically significant relationship, that is, the probability of finding a higher level of productivity increases with a higher presence of the above company.
Keywords: D21; E23; L1; 650; productivity by worker; competitiveness; Wal-Mart; commerce; productividad por trabajador; competitividad; Wal-Mart; comercio